ANALISIS POTENSI DISTRIBUSI AIR IRIGASI SISTEM IRIGASI TETES BERTINGKAT UNTUK USAHA TANI DI PERMUKIMAN PERKOTAAN - I Dewa Gede Jaya Negara; Heri Sulistiyono; Anid Supriyadi; I B Giri Putra; I Wayan Yasa; M R. Sepriadi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
Agricultural activities in urban housing need to be supported by adequate irrigation systems such as efficient drip irrigation. In addition, drip irrigation does not require a large area or large amount of water, but with limited land area and water sources, horticultural crop farming can be carried out. By using polybags as a planting medium and with drip irrigation, more planting points will be obtained. To obtain a guarantee that the multilevel drip irrigation system can be applied properly, it is necessary to test it so that the ability to use irrigation is known. This study aims to determine the ability of stratified drip irrigation on the distribution of irrigation volume and the provision of soil moisture (w) in polybags, at each level of polybag land. The research was conducted on land measuring 1m x 2m x 4 m, water source from 150 liter tank, irrigation network from Â¾â€, Â½â€, and Â¼â€ PVC pipe and 12 mm Netafim (NTF) drip pipe. Data analysis was carried out on uniformity, irrigation volume, soil moisture (w) and irrigation pattern. The irrigation test for 5 minutes showed that the average irrigation diversity was above 98% and the deviation of the irrigation volume for each level was an average of 15 ml. The resulting soil moisture levels 1, 2, and 3 are 13.4%, 5.5%, and 3.9%, respectively. To obtain the same irrigation volume, drip irrigation should be carried out in turns with different durations.